Encyclopedia of the Piano - Palmieri, Robert (New York Garland Publishing, 1996)
This comprehensive highly illustrated volume traces the evolution of this popular instrument and includes information on the fortepiano, player piano, electonic piano, and synthesizer. The over 600 articles cover such topics as artisans, composers, events, companies, instrument construction, culture and history, research discoveries, and future trends.
Keywords: Past; Piano; Keyboard; Music history